Duterte's pandemic populism: Strongman leadership, weak state capacity, and the politics of deployment in the Philippines - Julio C. Teehankee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The outbreak of the COVID-19 pandemic undermined the populist legacy of Philippine president Rodrigo R. Duterte. Despite implementing one of the longest and strictest lockdowns globally, the country has struggled with controlling the pandemic. While Duterte looks to have triumphed in his attack on human rights and press freedom, his government's record in combating the virus has been spotty at best. Yet Duterte's populism has proven to be resilient. He has remained extremely popular, with a September 2021 national survey reporting 81 per cent approval of his government's response to the pandemic and 91 per cent of respondents expressing trust in his leadership. The irony of Duterte's populist resilience amid his poor pandemic response serves to highlight his mastery of political deployment within a weak state. Two significant inputs are required to deploy state capacity into a range of outcomes: political coalitions (including leadership, classes, and parties) and a balance of social forces. The 'politics of deployment' depends on the quality of decision-making of state leadership and the political coalitions forged to support such decision-making. Decisions, in turn, depend on the balance of social forces-the resistance or support of various sectors in society. This paper will unpack Duterte's deployment of 'brute force governance' (which he earlier employed in his bloody 'war on drugs') in addressing the COVID19 crisis in the Philippines.
Keywords: B52; H10; H11; H12; 330; COVID-19; pandemic; Philippines; populism; Rodrigo Duterte